Pengaruh Implementasi Pembelajaran Pendidikan Agama Islam Secara Daring dan Kendalanya dalam Penguasaan Pengetahuan - Aprilatip Aprilatip (Eduprof : Islamic Education Journal, 2021)
The research objectives were (1) to determine the knowledge mastery ability of grade 9 students about KD 3.9 Understanding the provisions of the Hajj and Umrah pilgrimage (2) to analyze the differences in knowledge mastery from the first, second, and third daily assessments during online Islamic Education learning at KD 3.9 and (3) analyzing the obstacles faced in online Islamic Education learning in grade 9 at SMPN 1 Cidahu. The research method uses descriptive quantitative. The research subjects were 34 students of grade 9A. The data collection technique used the test method, questionnaire, interview and documentation. The data analysis technique used descriptive analysis and Friedman test. The results of the study were concluded (1) the results of the daily assessment 1 with an average of 80.97; PH2 average value 81.82; and PH3 with an average value of 81.88. Based on the results of the average daily assessment values above, it can be concluded that the highest average value is at PH3, (2) There is no significant difference from the average value between mastery of knowledge of PH1, PH2, and PH3 with a probability value of 0.687> 0 , 05 which indicates that the research hypothesis is rejected, (3) The obstacles that often arise during the implementation of online Islamic education learning in grade 9 SMP Negeri 1 Cidahu are inadequate internet packages for teachers and students, limited internet access by teachers and students, and teachers and students are not used to implementing online learning ABSTRAK Tujuan penelitian ialah (1) mengetahui kemampuan penguasaan pengetahuan siswa kelas 9 tentang KD 3.9 Memahami ketentuan ibadah haji dan umrah (2) menganalisis perbedaan penguasaan pengetahuan dari penilaian harian pertama, kedua, dan ketiga selama pembelajaran PAI secara daring pada KD 3.9 dan (3) menganalisis kendala-kendala yang dihadapi dalam pembelajaran PAI secara daring di kelas 9 SMPN 1 Cidahu.Metode penelitian menggunakan deskriptif kuantitatif.Subjek penelitian sebanyak 34 siswa kelas 9A. Teknik pengumpulan data menggunakan metode tes, angket, wawancaradan dokumentasi. Teknik analisis data menggunakan analisis deskriptif dan uji Friedman.Hasil penelitian disimpulkan (1) Hasil penilaian harian 1 dengan rata-rata 80,97; PH2 nilai rata-rata 81,82; dan PH3 nilai rata-rata 81,88. Berdasarkan hasil nilai rata-rata penilaian harian di atas maka dapat disimpulkan bahwa nilai rata-rata tertinggi pada PH3, (2) Tidak terdapat perbedaan yang signifikan dari nilai rata-rata antara penguasaan pengetahuan PH1, PH2, dan PH3 dengan nilai probabilitas 0,687 > 0,05 yang menunjukkan bahwa hipotesis penelitian ini ditolak, (3) Kendala yang sering muncul selama pelaksanaan pembelajaran PAI secara daring di kelas9 SMP Negeri 1 Cidahu adalah paket internet yang kurang mencukupi bagi guru dan siswa, keterbatasan akses internet oleh guru dan siswa, serta guru dan siswa belum terbiasa melaksanakan pembelajaran secara daring.